Sub-Inhibitory Concentrations of Mupirocin Strongly Inhibit Alpha-Toxin Production in High-Level Mupirocin-Resistant MRSA by Down-Regulating agr, saeRS, and sarA - Jin, Ye; Li, Meilan; Shang, Yongpeng; Liu, Li; Shen, Xiaofei; Lv, Zhihui; Hao, Zhihao; Duan, Jingjing; Wu, Yang; Chen, Chun; Pan, Jingye; Yu, Fangyou (Frontiers in Microbiology, 2018)
Mupirocin, a topical antibiotic, has been utilized for decades to treat Staphylococcus aureus skin infections, as well as to decolonize patients at risk of methicillin-resistant S. aureus (MRSA) infection. The aims of this study were to investigate the expression of α-toxin (encoded by the hla gene) in ten clinical MRSA strains in response to a sub-inhibitory concentration of mupirocin (1/32 minimum inhibitory concentration [MIC]) by using α-toxin activity determination and enzyme-linked immune sorbent assay (ELISA). Subsequently, real-time polymerase chain reaction (RT-PCR) was used to examine the expression of saeR, agrA, RNAIII and sarA genes under sub-inhibitory concentration of mupirocin in order to investigate the mechanism of action of this treatment regarding its strong inhibition of α-toxin expression. For all the strains tested, mupirocin dramatically reduced mRNA levels of α-toxin. The results indicated that α-toxin activity in mupirocin-treated groups was significantly lower than that in untreated groups. The results show that the levels of agrA, RNAIII, saeR and sarA expression significantly decrease by 11.82- to 2.23-fold (P<0.01). Moreover, we speculate that mupirocin-induced inhibition of α-toxin expression may be related to the inhibition of regulatory loci, such as agr, sarA and saeRS. More specifically, we found that the mechanism involves inhibiting the expression of agrA and RNAIII. In conclusion, sub-inhibitory concentrations of mupirocin strongly inhibit alpha-toxin production in high-level mupirocin-resistant MRSA by down-regulating agr, saeRS and sarA, which could potentially be developed as a supplemental treatment to control high-level mupirocin-resistant MRSA infection and reduce the risk of infection and colonization. Keywords: MRSA; sub-inhibitory concentrations; mupirocin; alpha-toxin; agr; saeRS; sarA;